Monoclonal antibody-based enzyme immunoassay for detection of porcine plasma in fish surimi - Raja NharI, Raja Mohd Hafidz; Khairil Mokhtar, Nur Fadhilah; Hanish, Irwan; Hamid, Muhajir (Taylor & Francis, 2018)
Detection of porcine plasma using indirect ELISA was developed using mAb B4E1 for the prevention of their usage in human food that creates religious and health conflicts. The immunoassay has a CV<20% and did not cross-react to other meat and non-meat proteins. The sensitivity of the assay is 0.25% (w/w) of porcine plasma in spiked raw and cooked fish surimi. The assay did not produce a false positive result for any of the commercial fish surimi tested that were not contain porcine plasma. Determination of a 60-kDa antigenic protein of porcine blood using Western Blot confirmed its presence in the plasma fraction of the porcine blood. Further proteomic analysis involving liquid chromatography-tandem mass spectrometry (LC-MS/MS) revealed the 60-kDa protein to be porcine serum albumin.